Aerobic bacterial pathogens in burn wound infections: experience in a teaching institution - Thomas, Bonnie J.; Arora, Balvinder Singh; Arora, Savita (International Journal of Research in Medical Sciences, 2021)
Background: Infections are a serious cause of burn mortality and morbidity. Post initial resuscitation burn wound infections account for 75% of burn mortality. With rising number of multidrug resistant pathogens and changing microbiological colonizers of the burn wound, the insight provided by documenting the pathogens will help streamline the management. The aim of our study was to isolate, identify and study the profiles of aerobic bacteria in patients with burn wound infections. Methods: This was a hospital based observational study carried out in the department of microbiology and department of burns and plastics, Safdarjung hospital after obtaining hospital ethical committee approval. Day 1, day 3, day 5 and day 10 swabs from burn sites were taken and processed after taking proper aseptic precautions from a total of 100 patients. Results: Most of the aerobic isolates were gram negative in nature with K.pneumoniae (27.43%) being the most common followed by P. aeruginosa (22.12%), S. aureus (14.15%), P. mirabilis (10.61%), Acinetobacter spp (10.17%), CoNS (8.40%), E. coli (3.53%), P. stuartii (1.32%), Enterobacter spp (1.32%), K. oxytoca (0.44%) and C. koseri (0.44%). Conclusions: We concluded the study recognizing K. pneumoniae as the most common isolate that cause burn wound infections. Further studies which include anaerobic isolates are required for identifying full range of organism profile of burn wound infections.